2018
DOI: 10.3390/sym10070233
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries of Differential Equations in Cosmology

Abstract: Abstract:The purpose of the current article is to present a brief albeit accurate presentation of the main tools used in the study of symmetries of Lagrange equations for holonomic systems and subsequently to show how these tools are applied in the major models of modern cosmology in order to derive exact solutions and deal with the problem of dark matter/energy. The key role in this approach are the first integrals of the field equations. We start with the Lie point symmetries and the first integrals defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 136 publications
(220 reference statements)
0
89
0
Order By: Relevance
“…(1) We write an ansatz for the generator of the form (27) defined on the configuration space. (2) We expand the symmetry condition (29) to obtain a polynomial depending on ξ(t, q), η i (t, q) and products of the generalized velocities, i.e. (q aqb ...).…”
Section: Finding Symmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) We write an ansatz for the generator of the form (27) defined on the configuration space. (2) We expand the symmetry condition (29) to obtain a polynomial depending on ξ(t, q), η i (t, q) and products of the generalized velocities, i.e. (q aqb ...).…”
Section: Finding Symmetriesmentioning
confidence: 99%
“…Let us now apply the symmetry condition (29) to the point-like Lagrangian (38). If symmetries exist, such a condition will fix the form of vector X as well as the form f (R, G).…”
Section: Noether Symmetriesmentioning
confidence: 99%
“…As it is pointed out in [25], we also note that the classical Noether symmetry approach with a boundary term K constrains the F(R, G) gravity as a selection criterion that can distinguish the F(R, G) models to utilize the existence of non-trivial Noether symmetries. In this study, we found the maximum number of symmetries as five at the non-vacuum case, but it is four at the vacuum case [28].…”
Section: Discussionmentioning
confidence: 55%
“…However, it is usually required a clever choice of cyclic variables because of that the equations for the change of coordinates have not a unique solution which is also not well defined on the whole space, and thus it is not unique to find those of the cyclic variables (see References [27] for details). Furthermore, we refer to the interested readers the recent review on symmetries in differential equations [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation